Thematic and Problematics of the Issue of Preschool Education in the Press of Uzbekistan (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study studies how issues of preschool education and upbringing are discussed in the press of Uzbekistan. The purpose of the study is to identify the existing problems and ways of development of the preschool education system through articles and materials in the press. The study used press materials, analyzed statistics and expert opinions. The results showed that there is a shortage of pedagogical personnel in the preschool education system, problems of improving the quality of education and the need to introduce modern methods. This study includes recommendations for improving the preschool education system.